Normality and Normalcy: A Case of -ITY/-CY Doublets in the BNCC - Jevrić, Tamara M. (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Corpus-based research into derivational morphology can explain how affixes function, answer questions about their productivity and its relation to their synonymy, and clarify the rivalry between certain affixes and their semantic distinction. The aim of this research is to establish the similarities and differences between the nouns normality and normalcy by contrasting the suffixes -ity and -cy they contain in the British National Corpus (BNC). The focus is on the collocates which precede the nouns and the sources in which they appear. The attempt is also to understand what characterises the suffixes and their distribution. By focusing on normality and normalcy, we examine how lexical items behave in an electronically-stored corpus and whether a strong connection between meaning and form manifests itself in different word patterns highlighting different aspects of meaning.
Keywords: corpus-based research; derivational morphology; normality and normalcy; suffixes -ity and -cy; BNC